(untitled) (Economics and region, 2022)
The proposed study is devoted to the legalization of the gambling business as a tool for filling the budget in the context of anti-crisis management. In the frame of this research the problem of gambling as a special subject of the governments scrutiny in all jurisdictions was determined. The relevance of the research topic results from the new approaches in the modern scientifical worldview due to the legalization of gambling, which was almost always accompanied by the government of an appropriate regulatory regime and structure. Many countries around the world have legalized gambling primarily because they see it as a tool for economic growth, the gambling industry has grown rapidly over the past two decades, due in large part to technological leaps in payment systems and software. Since the aggregate social costs of gambling are much lower than the aggregate social benefits, revenues from legal gambling are used as a source of filling local budgets. The high dynamics of market development shows that legal gambling in Ukraine is an attractive sector for investment. However, the tax burden and triple the initial license fee means that legal gambling operators, regardless of the amount of investment in their business, will take a long time to recoup them. In order to optimize the tax burden, the draft law 2713-d was registered, which will have significant positive consequences for the economy, namely the attraction of investments, in particular Western ones, in the sector of legal gambling, which will contribute not only to the filling of the state budget, but also to the creation of new jobs, as well as to the strengthening business activities in other industries with which companies from the gambling sector will interact. In terms of the distribution of state revenues from legal gambling, it is advisable to implement the positive experience of other countries. Highlighting theoretical approaches of research, practical results of the research can be used for overcoming the lack of budget funds with help of revenue that are generated from legal gambling and can be used to provide key services, including health and education, and support the economic development of local communities.